(3efgLjI GdHMK GdYdej aj GdYdhe GdELJeGYjI (B:s (3CSS YdejI hJOQjHGJ (B/s - (3RQhGJj, QTjOs ((3GdLRGFQ (B: s (3OGQ GdcJGH GdMOjK(B, s, 2020)
(3JfGhd gPG GdcJGH efgLjI GdHMK GdYdej aj GdYdhe GdELJeGYjI, MjK jTed GdaUd GdChdi ef gPG GdcJGH GdeQGMd GdChdi aj GdHMK hjTed cjajI GNJjGQ GdehVhY, hJMVjQ GdHMK, hJYdje bhGYO JHhjH GdHMK, bhGYO JhKjb GdHMK, NWI hagQS GdHMK(B. (3CeG aj aUhd GdePcQI GdQFjSjI aJTed aUhd GdePcQI Ch GdQSGdI Ch GdCWQhMI GdLGeYjI, CeG GdedMb hJe ajg YQV cjajI JbOje GdePcQI Ch GdQSGdI Ch GdCWQhMI CeGe dLfI GdefGbTI, MjK jJWdH Pdc JMVjQG GLJeGYjG hfaSjG hYdejG, ceG YQVfG efgLjI cJGHI eTQhY GdHMK, ceG PcQfG HGdMQha GdCHLOjI hHYV GdCQbGe GdQheGfjI fXQG dVQhQI Pdc aj GdHMK(B. s
(3GdeQGLY U(B.239 (3GdedGMb U(B.233s
Keywords: (3GdYdhe GdELJeGYjIs; (3WQb GdHMKs; (3efGgL GdHMK GdYdejs